The Effect of Math Anxiety on Boarding School Students' Mathematics Learning Outcomes during Online Learning - Hefri Asra Omika (Jurnal Pendidikan dan Pengajaran, 2022)
Currently, students face a lack of references to math anxiety in the context of boarding school education and online learning during the COVID-19 pandemic. This study aims to analyzes the effect of math anxiety on mathematics learning outcomes in boarding school students during online learning during the COVID-19 pandemic. The sample of this research consisted of 182 class XII students in boarding schools. Sample selection uses a simple random sampling technique. The instrument used was a math anxiety questionnaire from Cooke et al. and a mathematics learning outcome document. The results of the instrument reliability test with a Cronbach alpha value of 0.968. Data analysis used descriptive analysis, linear regression test, and independent-sample t-test. The results of this study indicate that (1) the level of math anxiety in boarding schools is in a low category, (2) math anxiety has a significant effect on student learning outcomes based on a linear regression significance value of 0.02 which is a smaller than 0.05, and (3) there is a significant difference between the math anxiety levels of male and female students, where female students have higher math anxiety levels.